Social and Cultural Development: Promoting Awareness Towards Inclusive Education - Rendon, Hazel Cres D.; Gutierrez, Jonabee M.; Dangcalan, Michelle E.; Eriman, Anna May G.; Caabas, Marife Z.; Villar, Edna E.; Mohammad, Nhelbourne K. (International Journal of Learning Reformation in Elementary Education, 2023)
This article aims to promote awareness of inclusive education. Education is every learner’s right, not a privilege. Inclusive education promotes equitable and quality education for everyone, all without being excluded, mainly for those with potential learning needs. It also enhances the awareness about the rights of every learner with a disability or difficulty accessing the same education services. It is shown that from the point of view of different educational researchers, a significant tool for promoting the awareness of inclusive education is the orientation from the school management or educational system on all of its subordinates discussing the scope of the curriculum and adequate dissemination of information regarding different strategies that are applicable in diverse learners. It is also revealed that the significance of inclusive education is a school that focuses on having an integrative, innovative, career-oriented, and harmonious teaching-learning process. It is shown that building relationships between the teachers and the learners is an essential psychological, social, mental, and emotional aspect of inclusive classes. Lastly, inclusive education significantly requires the involvement and support from the parents of learning disabilities children at all levels.